Pengaruh Pertumbuhan Ekonomi dan Inflasi terhadap Pertumbuhan UMKM di Provinsi Jambi Tahun 2020-2024 - Julia Nur Aini; Novi Mubyarto; Ogi Saputra (Jurnal Riset Ekonomi dan Akuntansi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy of Jambi Province. However, their growth is challenged by macroeconomic issues such as economic uncertainty and inflation fluctuations. This study aims to examine the effects of economic growth, as measured by Gross Regional Domestic Product (GRDP), and inflation on the development of MSMEs across the eleven regencies/cities in Jambi Province during the 2020–2024 period, both partially and simultaneously. The study employs a quantitative approach using panel data, combining five years of time-series data with cross-sectional data from the eleven regencies/cities. The data were obtained from the Central Bureau of Statistics (BPS) of Jambi Province and the Office of Cooperatives and MSMEs of Jambi Province. The analysis was conducted using multiple linear regression with panel data, and the most appropriate model was selected through the Chow test and Hausman test, both of which indicated the Fixed Effects Model (FEM) as the best specification. Due to indications of heteroskedasticity, the model was corrected using the Panel Estimated Generalized Least Squares (EGLS) method to ensure efficient estimates and satisfy the Best Linear Unbiased Estimator (BLUE) assumptions. The findings reveal that, partially, economic growth (GRDP) has a positive and statistically significant effect on MSME development (t-statistic = 7.954 > t-table = 2.006; p-value = 0.0000 < 0.05). Simultaneously, economic growth and inflation jointly have a significant effect on MSME development (Prob. F-Statistic = 0.000000). Therefore, this study concludes that economic growth is the primary driver of the increase in the number of MSMEs in Jambi Province, while moderate inflation does not hinder MSME development. The study recommends optimizing Islamic People's Business Credit (Sharia KUR), strengthening the hisbah function for market supervision, accelerating MSME digitalization, and establishing a Regional Regulation on Sharia MSME Development in Jambi Province.